An analysis for snap-through behavior of bi-stable hybrid symmetric laminate with cantilever boundary. (15th February 2021) - Pan, Diankun; Wu, Zhangming; Dai, Fuhong
Abstract: This paper focuses on a study of the snap-through behavior of a family of bi-stable plates constructed by hybrid symmetric laminates with a cantilever boundary. Involving shape change and actuation demand, a deep understanding of the snap-through behavior is of particular importance since this bi-stable laminate is often served as a host structure of energy harvester or a morphing structure. The snap-through behavior is obtained using two displacement-controlled finite element procedures provided in the commercial software ABAQUS and the results are verified by experiments. The entire equilibrium path of reaction force-displacement response with a couple of zero load crossings is captured by the 'Static, Riks' procedure to reveal the potential nonlinear structural behavior. The practical situation of the reaction force-displacement curve is obtained by the 'Static, General' procedure which exhibits consistent results with experiments. Several characteristics, such as snap-down, hysteresis, negative stiffness, and even zero stiffness are captured. A parametric study including lay-up design and length is also carried out using the finite element model and verified by experiments. The results show that the lay-up design not only can fundamentally change the snap-through response but also influences other characteristics of this bi-stable laminate including stable shape, and the length is a relatively reliable parameter to alter the snap-through features, e.g. peak force and hysteresis performance.